Fourier and Inverse Fourier Transform Model for Delayed Self-interferometry System - Ling Zhang; Weilin Xie; Yuxiang Feng; Zhangweiyi Liu; Haijun Zhou; Yinxia Meng; Yuanshuo Bai; Wei Wei; Yi Dong (IEEE Photonics Journal)
Understanding the effects of laser phase and frequency noise on laser interferometry is significant for evaluating the system performance. To precisely study the performance limit caused by laser frequency noise, here we propose and demonstrate a versatile model based on the Fourier and inverse Fourier transform (FIFT) method. This model, capable of estimating the beat note spectra of different delayed self-interferometry (DSI) with laser sources of arbitrary frequency noise properties, allows for accurate evaluations of the noise performance in a variety of interferometry based systems. Such a model has been experimentally validated using lasers with irregular frequency noise properties such as cavity stabilized fiber laser or laser under optical phase-locking, providing more detailed insight into the evolution of the frequency noise dynamics at different interferometric conditions. With average estimation goodness (AEG) of 0.9716 and computation complexity of $\mathcal {O}(N\text {log}N)$ , this model offers greater accuracy and lower complexity than conventional methods. It has also been confirmed that this model permits to distinguish the contributions from the laser frequency stability and other noise sources, which could be helpful for the noise analysis and performance optimization of the system.